ChemInform Abstract: A Polymer‐Supported Chiral Fluorinated Dirhodium(II) Complex for Asymmetric Amination of Silyl Enol Ethers. Issue 10 (7th March 2013) - Oohara, Tadashi; Nambu, Hisanori; Anada, Masahiro; Takeda, Koji; Hashimoto, Shunichi
Abstract Preliminary studies concerning the application of title catalyst (I) are presented.